Overview of web mining and its applications 1 - Mobasher, Bamshad (Henry Stewart Talks, 2008)
Data mining, Knowledge discovery in data viewed as a process, Web content mining, Web usage mining, Web structure mining, Web content mining, Web content mining, Data preparation and representation, Approaches and application, Clustered search results, Personalized content delivery, Web structure mining, Google's PageRank algorithm, Hubs and authorities, Web communities
Archived at 2022/03/17